To explore the relationship between energy transfer rate and impact sensitivity by the first-principle calculation method. (June 2023) - Bao, Shi-Yuan; Liu, Qi-Jun; Hong, Dan; Liu, Wei-Hong; Ma, Xiao-Juan; Liu, Fu-Sheng; Xing, Wei; Liu, Zheng-Tang
Abstract: To investigate the relationship between impact sensitivity and energy transfer rate, the energy transfer behaviors of seven energetic materials were estimated. We divide energy transfer in molecules into two parts, which are the intramolecular energy transfer and the outward energy dissipation between the molecules, respectively. We use new defined parameter T to reflect the rate of energy transfer within the molecule. The sound velocity is used to reflect the rate at which energy is dissipated out of the molecule. The results show that the faster the energy transfer and the slower the intermolecular dissipation, the more sensitive the energetic material is. Highlights: The relationship between energy transfer rate and impact sensitivity of seven energetic materials was studied. We define a parameter T related to Δω and the number of doorway modes to evaluate the transfer velocity of intramolecular vibration modes. We believe that the accumulation of energy within the solid molecule depends on the two parts T and Vm . The effects of T and Vm  on impact sensitivity were discussed.